Діалектна лексика як домінантна ознака ідіолекту Євгенії Ярошинської - Морараш, Г. (Філологічний дискурс, 2016)
У статті проаналізовано діалектну лексику як домінантну ознаку ідіолекту Є. Ярошинської, визначено тематичні групи діалектизмів на позначення: 1) назв людей за професією, за оцінними характеристиками; 2) назв одягу та прикрас; 3) назв побутових предметів; 4) назв будівель та споруд; 5) назв страв та напоїв; 6) назв дерев, кущів, рослин; 7) назв абстрактних понять тощо; на багатому фактичному матеріалі розглянуто частиномовну належність діалектизмів; за результатами спостережень зроблено висновок про те, що діалектна лексика, представлена в творчості Є. Ярошинської, виформовує ідіолект письменниці, відбиває особливості говірок південно-західного наріччя й передає локальні характеристики мовлення буковинців. The article analyzes the dialect vocabulary as a dominant feature of idiolect of Ye. Yaroshynska, the thematic groups of dialects to indicate are defined: 1) the names of people by the profession, according to evaluative characteristics; 2) the names of clothing and jewelry; 3) the names of household items; 4) the names of buildings and structures; 5) the names of foods and drinks; 6) the names of trees, shrubs and plants; 7) the names of abstract concepts, etc; on a rich factual material various parts of speech of dialecticisms are studied; based on observations it is concluded that the dialect vocabulary, presented in the works of Ye. Yaroshynska, creates idiolect of the writer, reflects peculiarities of dialects of southwestern subdialect and shows local characteristics of Bukovyna dwellers’ speech.